2005
DOI: 10.1111/j.1532-5415.2005.53308.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication Safety in Older Adults: Home‐Based Practice Patterns

Abstract: A substantial proportion of older adults on high-risk medications do not recall receiving instructions for the use of their medications and do not take advantage of existing systems for organizing medication regimens. Improved patient education and delivery of medication organization systems are immediate opportunities to potentially reduce the risk of medication errors in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 16 publications
2
72
0
3
Order By: Relevance
“…While further improvements might be made in the design of prescription drug labels, it is likely that patient counseling will also be needed to address health literacy deficits. Previous research has found physicians do not commonly review the instructions when prescribing medications, nor do pharmacists routinely verbally counsel patients when filling a prescription [26][27][28][29] . Both the American Medical Association and American Pharmacists Association recommend provider training in health literacy communication 'best practices' 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…While further improvements might be made in the design of prescription drug labels, it is likely that patient counseling will also be needed to address health literacy deficits. Previous research has found physicians do not commonly review the instructions when prescribing medications, nor do pharmacists routinely verbally counsel patients when filling a prescription [26][27][28][29] . Both the American Medical Association and American Pharmacists Association recommend provider training in health literacy communication 'best practices' 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 From a provider/system perspective, research suggests that physicians are missing opportunities to communicate with patients about medicine regimens. 7,8 As a result, information in the medical record may not be accurate and current. From the patient perspective, limited health literacy might be a less-recognized barrier to medication reconciliation.…”
mentioning
confidence: 99%
“…Other reported causes include failure to recall administration instructions, 10 to understand how to take medications, 22 to read medication label/insert 9 or to use a dose administration container. 10 Also reported are communication difficulties, 9,23 limited cognitive ability, 3 inability to read, 21,22 and the lack of a caregiver.…”
Section: Articlementioning
confidence: 99%
“…However, there is a relative paucity of reports examining therapeutic errors, particularly outside of acute care settings where the majority of medications are taken. 2,[7][8][9][10][11] Accordingly, the epidemiology of therapeutic errors in the community setting is poorly understood. 5,11 This precludes the accurate determination of high-risk patient groups and factors that may contribute to errors e.g.…”
mentioning
confidence: 99%